PENERAPAN K3 (KESEHATAN DAN KESELAMATAN KERJA) DALAM UPAYA MEMINIMALISIR KECELAKAAN KERJA DI PT XYZ - Firdayanti, Elvira; Septihani, Nenden; Apriyanty, Sri Ayu; Suyono, Annisa Maharani (LPPM Universitas Bina Bangsa, 2024)
Apart from causing losses to workers, work accidents will also result in budget losses for the company. This is caused by the K3 implementation system which is still not running within the company. The number of work accidents and various K3 threats in Indonesia is still quite high, various work accidents still often occur in the production process, especially in the manufacturing industry. This research uses a qualitative descriptive approach through case studies. This research's data collection technique uses a questionnaire technique to obtain data. Based on the results obtained, the implementation of K3 in this research is with commitment from PT XYZ is a very important thing to be done by central management, then stated in the form of policies related to K3 to management at PT XYZ